Beyond Envy: Rethinking Comparison Culture through Syahrur’s Theory of Limits - Huda, Muhammad Fathul; Sihabudin, M. (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study examines comparison culture in the digital age and proposes a Qur’anic ethical framework through a reinterpretation of Q. An-Nisa’: 32 using Muḥammad Syahrur’s naẓariyyat al-ḥudūd (theory of limits). Social media has intensified social comparison practices, often leading to insecurity, anxiety, and low self-esteem. Although Social Comparison Theory explains how comparison functions, it provides limited normative guidance for regulating such behavior. This qualitative library research integrates Qur’anic exegesis with contemporary social theory. The study analyzes Q. An-Nisa’: 32 through contemporary tafsir, particularly socio-ethical (adab ijtimā‘ī) and spiritual (tasawuf) perspectives found in the works of al-Ālūsī, al-Marāghī, and M. Quraish Shihab, and reinterprets them through Syahrur’s theory. The findings show that the Qur’an does not prohibit comparison altogether but regulates it within ethical boundaries: ḥadd adnā, which limits destructive envy, and ḥadd a‘lā, which permits constructive comparison that encourages self-improvement.